Selection of risk response actions considering risk dependency. Issue 10 (7th November 2016) - Zhang, Yao; Zuo, Fei
Abstract : Purpose: The purpose of this paper is to propose a method to address the problem of selecting risk response actions (RRAs) considering the risk dependency that is seldom considered in the existing studies. Design/methodology/approach: First, a method based on the Measuring Attractiveness by a Categorical-Based Evaluation Technique (MACBETH) is proposed to measure the dependencies between the risks, and then a preference coefficient denoting the relative importance of the risk dependency is introduced. Besides, an exponential utility function is used to describe the project manager's (PM) risk-averse behaviour. Finally, a mathematical model that incorporates the risk dependency and risk preference of the PM is constructed for selecting the RRAs. Findings: Risk dependency plays an important role in the process of RRA selection. First, more expected utility can be obtained when the risk dependency is considered. Second, more attention should be paid to the risk dependency for coping with critical risks when the budget is tight. Practical implications: This method can be applied to determine the RRAs when the risk dependency exists between the project risks. Originality/value: This paper proposes a model to select RRAs with consideration of the risk dependency, which is an important issue from a theoretical as well as a practical perspective in project risk management.